Стійкість розв’язків рівняння Річардса — Клюта - Колесников, В.А.; Ляшко, С.І. (Доповіді НАН України, 2023)
Наведено результати стійкості для розв’язків рівняння Річардса — Клюта під впливом збурень у початкових та крайових умовах. Метою статті є доведення апріорних оцінок варіації розв’язку, які виникають внаслідок збурень у початково-крайових умовах. Доведено основний результат обмеженості варіації розв’язку лінійною функцією від варіацій початково-крайових умов. Розглянуто випадок неоднорідного пористого середовища. The stability results of the Richards — Klute equation’s solution under perturbations of initial and boundary conditions are provided. The purpose of the article is to establish a priori estimates of the solution’s variation resulting from perturbations in the initial and boundary conditions. The primary finding demonstrates the boundedness of the solution’s variation by a linear function of the variation in the initial and boundary conditions. The case of a non-homogeneous porous medium is also examined.